2022
DOI: 10.1038/s41598-021-04628-3
|View full text |Cite
|
Sign up to set email alerts
|

Herbivorous fish (Medialuna ancietae) as a sustainable alternative for nutrition security in Northern Chile

Abstract: Sustainability in aquaculture is a necessity of the future, not only as the most promising means of supplying the protein that the world will require to feed its growing population but to offer needed conservation of the world’s ocean resources. The use of wild fish inputs in farm-raised fish outputs has been a primary concern of sustainability in aquaculture production. Herbivorous fish are more efficient converters of protein into fish flesh. Species of the genus Medialuna fish have been reported as a fast-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In this study, there were 38 main species of fish in the studied, and their carbon sources were POM, periphyton, phytoplankton, higher aquatic plants, zooplankton, and benthic organisms. Some studies have shown that Tilapia is mainly herbivore: its main food sources are reported to be algae and plant-based substances in water, and sometimes zooplankton [54][55]. However, Fetahi et al [8] detected a significant relationship between the carbon source and body length of Tilapia.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%
“…In this study, there were 38 main species of fish in the studied, and their carbon sources were POM, periphyton, phytoplankton, higher aquatic plants, zooplankton, and benthic organisms. Some studies have shown that Tilapia is mainly herbivore: its main food sources are reported to be algae and plant-based substances in water, and sometimes zooplankton [54][55]. However, Fetahi et al [8] detected a significant relationship between the carbon source and body length of Tilapia.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Auth...mentioning
confidence: 99%